2021
DOI: 10.48550/arxiv.2108.01912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internal Video Inpainting by Implicit Long-range Propagation

Abstract: Inpainting on 4K videos3840 pixels 3840 pixels (d). Object removal with a single-frame mask Given a mask on a single frame Results of other frames without labeled masks (c). Different domainsAutonomous Driving Anime Old Movies Figure 1: Ours results on (a) hard video sequences in DAVIS [29], (b) a 4K-resolution video, (c) videos from different domains [7], and (d) a video with a single-frame mask. Zoom in for details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Subsequently, the video inpainting model processes the RGB images and mask images obtained from the CNN network to generate restored images. The image restoration model we utilize is based on IIVI from [30], which produces high-quality restored images in scenarios with minimal background changes. In the practical application of SLAM systems, scenarios often involve significant changes in the scene, its immediate use for localization and map reconstruction is not feasible; hence, evaluation is essential.…”
Section: System Descriptionmentioning
confidence: 99%
“…Subsequently, the video inpainting model processes the RGB images and mask images obtained from the CNN network to generate restored images. The image restoration model we utilize is based on IIVI from [30], which produces high-quality restored images in scenarios with minimal background changes. In the practical application of SLAM systems, scenarios often involve significant changes in the scene, its immediate use for localization and map reconstruction is not feasible; hence, evaluation is essential.…”
Section: System Descriptionmentioning
confidence: 99%
“…Some recent research results [10][11][12], in particular, have shown that deep learning methods have excellent repair capabilities. Furthermore, video repair and related technologies can also be used for tasks such as eliminating watermarks [13], object removal [14], and movie special effects [15].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent research results [10][11][12], in particular, have shown that deep learning methods have excellent repair capabilities. Furthermore, video repair and related technologies can also be used for tasks such as eliminating watermarks [13], object removal [14], and movie special effects [15].…”
Section: Introductionmentioning
confidence: 99%